2016
DOI: 10.3892/mco.2016.974
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral hemorrhage-related differences in the expression of vascular endothelial growth factor, basic fibroblast growth factor and thioredoxin reductase 1 in human glioblastoma

Abstract: The present study was designed to evaluate the expression of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF) and thioredoxin reductase 1 (TrxR1) in glioblastoma multiforme (GBM) with and without intratumoral hemorrhage. Surgically resected human GBM samples from 20 patients who underwent surgery at our institute were extracted from the histopathological specimens and divided into two groups. A total of 10 samples from each type of GBM (World Health Organization grade IV, intrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The patient number in this study compares well against others that have sought to examine Trx system in GBM, i.e. the studies from Kaya et al [30] and Kemerdere et al [21] which included 20 and 27 GBM patients, respectively.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The patient number in this study compares well against others that have sought to examine Trx system in GBM, i.e. the studies from Kaya et al [30] and Kemerdere et al [21] which included 20 and 27 GBM patients, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…A study investigating 40 GBM patients showed significantly higher TrxR expression in primary GBMs with TrxR expression highly correlating with the Ki-67 index, but the study also did not assess for associations with patient survival [29]. A further study assessed TrxR in 20 GBM patients, showing higher TrxR expression in GBMs containing intratumoural haemorrhage, suggesting a role for TrxR in the promotion of tumour angiogenesis and growth, but again, associations with patient survival were not presented [30]. The number of adult GBM patients included in the current study (n = 18) could be regarded as being rather small however the low incidence of this tumour type should be borne in mind.…”
Section: Discussionmentioning
confidence: 98%
“…In mouse lung cancer cells, KO in mitochondrial TrxR alters cell redox status, stabilizes prolyl hydroxylases, and inhibits HIF-1 cascade, suppressing tumor angiogenesis [109]. In the case of humans, in glioblastomas with intratumoral hemorrhage there is an increase in the expression of VEGF and TrxR1, which can be related to an increase in tumor angiogenesis [110].…”
Section: The Thioredoxin Systemmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most aggressive and common form of glioma, being responsible for 3–4% of all cancer-related deaths ( Carlsson et al, 2014 ; Kaya et al, 2016 ). The risk of prevalence increases with age, being more common in people aged 60–79 years ( Kyani et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%